2017
DOI: 10.3390/ijerph14050470
|View full text |Cite
|
Sign up to set email alerts
|

Does Unstable Employment Have an Association with Suicide Rates among the Young?

Abstract: Although a growing body of literature has indicated that unemployment has a positive association with suicide, the dynamic aspects of unstable employment have not yet been considered in suicidology. This study explored the association between employment stability and completed suicide among people aged 25–34 years in 20 OECD (Organization for Economic Cooperation and Development) countries with time-series data (1994–2010). In order to consider the different aspects of unstable employment, we tested the impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 36 publications
1
25
2
2
Order By: Relevance
“…The empirical results presented in our study mirror and reflect the ones presented by Gerdtham and Johannesson (2), Ruhm (10), there is indeed a dual-link between unemployment rates and suicide rates both in the short run. Yet, it is also important to note that our empirical findings are inconsistent with those of Neumyer (45), Andrés (46), and Kim and Cho (47). Due to the advanced and comprehensive techniques and methods applied in our study, we believe the findings presented in our research to be more reliable and dependable.…”
Section: Resultscontrasting
confidence: 71%
“…The empirical results presented in our study mirror and reflect the ones presented by Gerdtham and Johannesson (2), Ruhm (10), there is indeed a dual-link between unemployment rates and suicide rates both in the short run. Yet, it is also important to note that our empirical findings are inconsistent with those of Neumyer (45), Andrés (46), and Kim and Cho (47). Due to the advanced and comprehensive techniques and methods applied in our study, we believe the findings presented in our research to be more reliable and dependable.…”
Section: Resultscontrasting
confidence: 71%
“…In fact, as research evidence showed (e.g. Kim & Cho, 2017), unstable employment is better predictor of suicide rates. However, some studies (e.g.…”
Section: Na -Data Not Availablementioning
confidence: 95%
“…persons descendent of who were once part of the Tawantinsuyu, the Inca Empire in the Central Andes; see García Moritán & Cruz, 2011). Despite that these aspects lead to suppose that the relevance of job instability in mental health-related problems, as it is suicide, may be not so clear, a recent report of the Organization for Economic Cooperation and Development (OECD) states out that it is instability in employment, rather than unemployment itself, the factor that would be associated to high rates of suicide in the youngest population (Kim & Cho, 2017). It seems necessary to replicate this study on suicide attempts because Argentina currently undergoing a major economic crisis that is deeply impacting on employment (i.e.…”
Section: Discussionmentioning
confidence: 99%